Integrative governance: The relationships between governance instruments taking center stage. (December 2018) - Visseren-Hamakers, Ingrid J
The fragmentation and complexity of governance are well recognized among scholars and policy makers. The debate on fragmentation has itself, however, also remained rather fragmented. This has inhibited the drawing of common lessons among the different communities, and has delayed the development of more concerted efforts to enhance synergies and address trade-offs between different societal goals. In order to move forward, this theme issue shows that the various disconnected debates are in essence trying to do the same thing—contribute to the discussion on the relationships between governance instruments. In order to do so, it is based on and advances the notion of Integrative Governance, defined as the theories and practices that focus on the relationships between governance instruments and/or governance systems. The theme issue serves the debate in two ways: (1) it contributes to the "defragmentation" of the debate by bringing together the different concepts and approaches used to study Integrative Governance and (2) it furthers the debate by addressing the main gaps in the Integrative Governance literature. Each article contributes to both aims of the theme issue by making conceptual links between the different approaches, and by addressing multiple gaps in the literature. As such, the theme issue as a whole contributes to a better understanding of the relationships between governance instruments, with a view to enhance these relationships and governance performance.